Framework of Teacher’s Knowledge: Concerns for Teacher Preparation Courses - Goswami, Richa (Voices of Teachers and Teacher Educators, 2018)
Teachers are the most important factor in the educational outcomes and learning levels achieved by any child, class or school. The paper presents a framework for teacher’s knowledge and is based on the analysis of a small study assessing the knowledge of the teacher’s from a few schools of Udaipur, Rajasthan. The findings of the study raise some pertinent recommendations and areas of concerns to be included while planning pre-service and in-service teacher capacity building programmes.